Gender mainstreaming for food security and poverty reduction programs in Asia and Africa - Hanjra, Munir A.; Zafar, M. I.; Batool, Z.; Nawaz, N.; Maann, A.A.; Ayalew, Z.; Alemu, B.A. (2013)
Gender is a socially constructed concept. It refers to the social, behavioral, and cultural norms, attributes, and expectations associated with being a woman or a man. Gender equality refers to how these aspects determine how women and men interact with each other and to the resulting differences in economic opportunities, endowments, agency and overall wellbeing outcomes for men and women. Gender mainstreaming refers to making general policies gender-smart - at various level of governance - to target the gender differentiated impacts and outcomes and implementing public policies and international development cooperation in a more strategic way that also improves gender equality and makes policies more effective in closing the key gender gaps even if their objectives has nothing to do with gender. Gender equality ranks high on the global development agenda and evidence-based gender targeting is emerging as a key criteria in international development assistance programs such as those for enhancing food security and reducing poverty and the broader development goals such as those set by the MDGs to 2015 and beyond. This chapter presents evidence on gender equality issues to highlight the key gender gaps such as assets, education, health, land, labor and commodity markets, and participation into decision making through six case examples from Asia and Africa. The case examples from Asia come from Pakistan and India, while the case examples from Africa are from Ethiopia and Zimbabwe. These case examples illustrate that gender gaps are huge and targeted interventions and gender mainstreaming can enhance economic opportunity, endowments, and agency of women. What is needed is the political will along with more funding, better data on gender, evidence, and global partnerships.